BRAND SATISFACTION MEMEDIASI PENGARUH SELF CONGRUITY TERHADAP BRAND LOYALTY - Nurkholish Majid; Sunaryo Sunaryo; Ananda Sabil Husein (MIX: JURNAL ILMIAH MANAJEMEN, 2018)
Abstract. Research aim to analyze 1) influence of actual, ideal, social and social ideal self-congruity on Iphone brand satisfaction. 2) Influence of actual, ideal, social and social ideal self-congruity self-congruity on Iphone brand loyalty. 3) Influence of brand satisfaction on Iphone brand loyalty. 4) The role mediation of brand satisfaction within influence of actual self-congruity, ideal self-congruity, social self-congruity, social ideal self-congruity on Iphone brand loyalty. Sample has taken by using non probabilty sampling with purposive sampling technique. Respondents are Iphone user in Malang City who made personally purchase decision with has used Iphone about 1 year. Research’s samples are 140. The hypothesis tested by Partial Least Square analysis. The research results actual, ideal and social ideal self-congruity influence on brand satisfaction then brand satisfaction influence on brand loyalty. Brand satisfaction had mediation within influence of actual, ideal dan social ideal self congruity on brand loyalty.